The Effects of Auditor Social and Human Capital on Auditor Compensation: Evidence from the Italian Small Audit Firm Market - Pietro A., Bianchi; Trombetta, Marco; Carrera, Nieves (Taylor & Francis, 2019)
This study examines whether social and human capital influence the compensation of individual auditors in the small audit firm market. We employ a sample of Italian auditors and use measures from the network and auditing literatures to capture their professional connections, representing social capital, and their industry expertise, representing human capital. Our findings show a positive and economically meaningful association between these individual attributes and auditor compensation. We run several tests to address potential endogeneity issues in our research design. Our results suggest that, in the small audit market, clients perceive as valuable those auditors with higher social and human capital, and as a result, are willing to pay a premium for these specific auditor attributes.
Keywords: Small audit firm market;Auditor compensation;Audit fees;Social capital;Human capital; Small audit firm market; Auditor compensation; Audit fees; Social capital; Human capital; 53 Ciencias Económicas::5303 Contabilidad pública; ODS 8 - Trabajo decente y crecimiento económico